Penatalaksanaan kandidiasis oral disebabkan Candida tropicalis pada anak dengan gangguan sistemik - Cane Lukisari; Dwi Setyaningtyas; Mintarsih Djamhari (Journal of Dentomaxillofacial Science, 2010)
Oral candidiasis is an oral mucosal infection caused by Candida albicans (CA) ornon-Candida albicans Candida (NCAC). C. tropicalis (CT) is most virulent NCACbecause it has the most adherence ability to epithelial cells in vitro as well as mediumlevel proteinase secretion. In addition, CT is the second most common colony found inhuman. Although incidence rate of oral infection was low, this species has virulencepotency, lately reported as the mayor cause of candidemia in immunocompromisedpatients. This paper reports and discusses oral candidiasis due to CT in a child whosuffered anemia with clinical sign of malnutrition. Oral nystatin suspension is therapyof choice because of patient well response, and in vitro studies reported lack ofresponse of fluconazole to candidemia due to C.tropicalis. However, nystatin oralsuspension, should be synchronized with hygiene optimalization of elimination ofpredisposition factors, and supportive therapy would provide a good prognosis.